The Effectiveness of Positive Feedback in Teaching Speaking Skill - Muhsin, Arief (Lingua Cultura, 2016)
The research was aimed at finding out the students’ responses and perceptions toward the corrective feedback given in teaching speaking activity. The research applied quantitative methods by sending questionnaires to 70 students. The students’ responses and perceptions for teacher’s corrective feedback indicated that students think their spoken error should be corrected. In addition, the students want their teacher focus more on. They also agree if their friends should correct their error. The most popular corrective feedbacks in teaching speaking are the explicit correction, elicitation, and repetition. They have an effective function in detecting the students’ mispronunciation and low accuracy and fluency. The other corrective feedback like implicit correction, recast, clarification request, and metalinguistic feedback are not favored because the percentage is lower than other corrective feedback. It indicates that not all of corrective feedback is effectively used in speaking.